2006
DOI: 10.1111/j.1447-0349.2006.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Demographic factors and clinical correlates of burden and distress in relatives of service users experiencing schizophrenia: A study from south‐western Nigeria

Abstract: Caregivers burden is an important area of clinical work that is often neglected, particularly in relatives of patients with psychosis. The aim of the present study is to examine if some demographic factors and symptoms of illness bear a relationship with burden and distress levels in their caregivers. This cross-sectional study involved patients with chronic schizophrenia and their relatives. The Carer Burden Index and the 30-item General Health Questionnaire was used to assess burden and distress in relatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 26 publications
4
27
0
Order By: Relevance
“…This speculation is illustrated in the findings of a Nigerian study which reported that despite the high levels of burden experienced, families expressed the wish to continue caring for their relatives in the communities. 8 Since caregiving to mentally ill patients can also lead to positive and rewarding experiences on the part of relatives, it is therefore not always exclusively burdensome. 13 The action taken by relatives was generally reflective of the level of effect on the family and different coping strategies were used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This speculation is illustrated in the findings of a Nigerian study which reported that despite the high levels of burden experienced, families expressed the wish to continue caring for their relatives in the communities. 8 Since caregiving to mentally ill patients can also lead to positive and rewarding experiences on the part of relatives, it is therefore not always exclusively burdensome. 13 The action taken by relatives was generally reflective of the level of effect on the family and different coping strategies were used.…”
Section: Discussionmentioning
confidence: 99%
“…As observed by another study, since relatives continue to play a caregiving role for patients experiencing a mental illness, there is need to focus on specific interventions that would reduce their high levels of distress and burden. 8 At the same time, the emotional and social impact of the mental illness on children in particular, and the family as a whole should be addressed, given that mental illness has been found to have a detrimental effect on children. 4,17 Other studies have suggested that even in a society with strong family networks, family psychoeducation on the nature of mental illness and dealing with its stigma and family burdens be used as an intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These relatives experience burden due to their relationship with the mentally ill person (Foldemo, Gullberg, Ek, & Bogren, 2005;Hadryś, Adamowski, & Kiejna, 2011;Ivarsson, Sidenvall, & Carlsson, 2004;Ukpong, 2006), which affects several areas of their everyday lives (Schmid, Spiessl, Vukovitch, & Cording, 2003). Burden is found to be composed of the impact that a person's mental illness has on relatives' marital relationship, appreciation for caring, and relationships with others, and is influenced by the perceived severity of the disease, and the relatives' sense of well-being (Sell, Thara, Padmavati, 704 B. M. WEIMAND ET AL.…”
mentioning
confidence: 99%
“…Most studies conducted in Nigeria on caregiver burden have been among relatives of patients with schizophrenia, with a dearth of literature on relatives of patients with bipolar affective disorder (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%